ANALYSIS OF THE USE OF ELECTRONIC PAYMENT SYSTEMS (E-WALLETS) AS A MEDIATOR OF FINANCIAL SATISFACTION FOR STUDENTS IN THE CITY OF BANDUNG - Damara Kapila Devi; Andrieta Shintia Dewi (SEAN Institute, 2023)
In recent years, Indonesia's population of internet users has steadily grown. This internet usage promotes the growth of e-commerce or inflammation. The volume of payments made via electronic payment systems has expanded along with Indonesia's expanding e-commerce economy. Students currently use the most electronic payment solutions. Students find it appealing to use electronic payment systems to make payments because of some of the characteristics that can give them financial happiness. One of the most popular electronic payment methods is the e-wallet. The purpose of this study is to ascertain how electronic payment systems affect students' financial satisfaction in Bandung City by mediating the effects of financial advice, financial anxiety, and financial capability. This research is a quantitative study, with a population of students in Bandung City aged 18-24 years. Purposive sampling was used to do the sampling and collected 400 samples. This study uses Structural Equation Modeling (SEM) analysis. The results of this study indicate that all variables have a significant influence on other sub-variables in the study, because they have a t-statistic value greater than the t-table value of 1.96.